THE PHILOSOPHY OF HRYHORII SKOVORODA IN THE CONTEXT OF HUMANCENTRISM - Василь Кремень (National Academy of Educational Sciences of Ukraine, 2022)
Through the prism of the Ukrainian philosophical thinking issues, the article highlights the philosophical position of Hryhorii Skovoroda, which is based on clarifying the specifics of a particular human personality and focuses on the inner world of a person, the world of the "soul" and "heart". According to H. Skovoroda, the "philosophy of the heart" is a statement of a new approach to understanding a person, the meaning of his existence and destination in the world. It is proved that such a cordocentric approach has a long national tradition and was initiated in the early literature of the proto-Ukrainian society of Kyivan Rus. It is substantiated that a characteristic feature of H. Skovoroda's philosophical system is the joining of a man and the world. This means creating a coherent philosophy that integrates ethics, ontology, philosophical wisdom, and moral behaviour in the philosophical dimension. H. Skovoroda appeals to the "voice of the heart", which confirms the begin of developing his humancentrism on the national ground and acts as an alternative to the rationalist and objectivist method precisely in defending the fundamental importance, the primacy of the individual and personal, and cultural and multivocal uniqueness of human existence.